Merkantilisme Dalam Perspektif Ekonomi Islam: Analisis Dampak Dan Kritik - Fatimatuz Zahro; Nur Hasan Busri; Tahta Alfina Nada Besari; Muhammad Ijal Khoiron; Muhammad Ifan; Putri Catur Ayu Lestari (Jurnal Ekonomi dan Bisnis Digital, 2025)
Islamic economics has grown rapidly worldwide as an alternative to conventional economic systems. However, it also faces challenges when dealing with existing economic frameworks such as mercantilism. Mercantilist theory asserts that government intervention and international trade increase a nation's wealth. This study uses a qualitative approach and a literature review method to analyze Islamic economic perspectives on mercantilism. The research aims to explore relevant Islamic economic principles and evaluate how mercantilism influences the modern economy. The data used in this study consists of secondary sources collected from articles, books, journals, and other literature discussing mercantilist theory and Islamic economic views on mercantilism. Data were gathered through library research and documentation. The findings indicate that Islamic economics opposes mercantilist methods, which prioritize monetary gain without considering justice and morality. Islamic economics emphasizes that in economic activities, fairness, honesty, and societal welfare are essential. The study also found that mercantilism can lead to economic inequality and social instability. As a result, Islamic economics offers more just and balanced alternatives, such as zakat, charity (sadaqah), and endowments (waqf). The study further analyzes Islamic economic criticisms of mercantilism, which include its focus on national wealth accumulation, excessive government intervention, and economic disparities. Islamic economics stresses the importance of balancing national and individual interests and ensuring equitable wealth distribution. It is hoped that this research will contribute to the advancement of Islamic economics and increase awareness of the importance of morality and justice in economic activities.